STUDI PERTUMBUHAN DAN PERKEMBANGAN KONDROSIT EMBRIO AYAM DALAM KULTUR DENGAN ASAM BORAT - Nur Ducha; Mammed Sagi; Istriyati (The East Java Biological Society, 2007)
The teratogenisity mechanism of boric acid is less known. There are contradictory observation on the effect of boric acid on the fetus malformation. An observation reported that boric acid is bound to the riboflavin and this complex causes a riboflavin deficiency on fetus. However, the other observation suggested that the present of riboflavin and boric acid had no decresed malformation on fetus, but increased malformation. It is giving an idea that the one of teratogenisity mechanism of boric acid may the biological mechanism to the target cells. The goal of this study was to evaluate the effect of boric acid on the growth and development of cultured chick embryo chondrocytes. Chondrocytes were dispersed from sternal cartilage of 12-d chick embryos (Gallus gallus). Randomized completely design was used to arrange this treatment with five replicates for each treatment. The dosage of boric acid were 10, 20, 40, 60, 80, and 100 μg/ml. The cultures were observed on 1, 3, 5, 7, 9 day after boric acid treatment, including: the cell proliferation, cell adhesion, cell attachment and colony formation. The data were analyzed descriptively. Result of this experiment showed that on high dose (80 and 100 μg/ml) cell adhesion was not formed, therefore the colony was not formed, and formed vacuola in the cell. This study indicated that boric acid on the high dose can inhibit the cell proliferation, cell adhesion, cell attachment and colony formation.